Odpowiedzi

2009-11-08T22:01:29+01:00
[(4x²-25) - (2x - 5)] * [(4x²-25) + (2x - 5)] = [(2x-5)(2x+5) - (2x - 5)] * [(2x-5)(2x+5) + (2x - 5)] = (2x - 5)(2x+4)(2x-5)(2x+6)
Najlepsza Odpowiedź!
2009-11-08T22:02:27+01:00
Skorzystajmy ze wzoru skróconego mnożenia:
a² - b² = (a + b) * (a - b).

(4x² - 25)² - (2x - 5)²=
((4x² - 25) + (2x - 5)) * ((4x² - 25) - (2x - 5))=

Z tego samego wzoru mamy:
4x² - 25 = (2x)² - 5² = (2x + 5) * (2x - 5)

Zatem:
((4x² - 25) + (2x - 5)) * ((4x² - 25) - (2x - 5))=
((2x + 5) * (2x - 5) + (2x - 5)) * ((2x + 5) * (2x - 5) - (2x - 5)) =
(tutaj wyciągniemy wspólny czynnik przed nawias)
[((2x + 5) +1) * (2x - 5)] * [((2x + 5) - 1) * (2x - 5)] =
(2x + 6) * (2x - 5) * (2x + 4) * (2x - 5)